Effect of Probiotic Addition EM-4 (Effective Microorganism-4) on Feed to Growth, Food Conversion Ratio and Survival Rate of Common Carp Larva Cyprinus carpio L. - Abdillah, Abdillah; Madinawati, Madinawati (AgriSains, 2020)
The problem that often becomes an obstacle in common carp culture is that the artificial feeding of common carp seeds has not yet had an optimal effect on survival and growth rates. due to the digestive system of seeds has not morphologic or physiologic differentiated, so the ability of seeds to digest feed still requires the addition of supplements such as probiotics. The research aims to analyze the effect of EM-4 probiotics addition on feed to growth SGR, FCR and survival rate of common carp seeds. The study was conducted in April to May 2019 at the Water Quality and Aquatic Biota Laboratory, Tadulako University. The study used a Completely Randomized Design consisting of 5 treatments and 4 replications. The treatments in this study were variations in the dose of EM-4 mixed addition in commercial feeding: A (0 ml/kg of feed); B (2 ml/kg of feed); C (6 ml/kg of feed); D (10 ml/kg of feed); E (14 ml/kg of feed). Data analysis used ANOVA and continued with LSD tests. The results showed that the use of EM-4 probiotics in feed significantly affected (P <0.05) on SGR, FCR and survival rate. Treatment D (10 ml / kg of feed) was the best treatment that resulted in SGR 0.014%, absolute weight growth of 7.775 g, FCR of 0.350 and 95% survival rate.